Estrategias ecológicas y ecoturismo del Recinto Soledad Chica en el cantón Simón Bolívar - Vargas Estrada, Blanca Flor (2021)
The deterioration of the environment is evidence of inadequate practices towards natural resources. Thus, sustainability arises to promote the balance of ecosystems, through the implementation of ecological strategies for the preservation of each natural space. The present analysis is about generating ecological strategies for the ecotourism development of the Soledad Chica area, in the Simón Bolívar canton. This research has a mixed approach to collect, analyze and interpret qualitative data through the development of an observation sheet and quantitative data through a survey of 99 people from the local community, the result showed that most of them carry out good environmental practices, but training is required for the community to improve them and venture into ecotourism.